2015
DOI: 10.1186/s12886-015-0097-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary open angle glaucoma in northern Nigeria: stage at presentation and acceptance of treatment

Abstract: BackgroundTo determine the stage of primary open angle glaucoma at presentation at a tertiary eye unit, to assess patient’s knowledge of glaucoma and acceptance and subsequent adherence to treatment.MethodInformation collected prospectively on new glaucoma patients aged 30 or more years included distance from residence and what they knew about glaucoma and its treatment. Treatment offered took account of disease severity and socioeconomic factors. Reasons for not accepting surgery were recorded. At follow up i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 36 publications
7
69
2
Order By: Relevance
“…Patients with POAG need to be identified early through adequate screening (5,16) . In Nigeria, many studies (17,18,19) have indicated that patients with glaucoma present late to the hospital. Therefore, ceasing every opportunity to screen those at higher risk will help in identifying those with the disease early and treat them accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with POAG need to be identified early through adequate screening (5,16) . In Nigeria, many studies (17,18,19) have indicated that patients with glaucoma present late to the hospital. Therefore, ceasing every opportunity to screen those at higher risk will help in identifying those with the disease early and treat them accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, 81% of those aware of family history of Glaucoma reported that they had gone for screening for the disease. In Nigeria, poor knowledge of glaucoma has been identified as a major factor associated with late presentation of glaucoma patients (18,19) . A robust population-based study in Nigeria showed that the prevalence of glaucoma was 5.02% with 86% of it being the open angle (4) .…”
Section: Discussionmentioning
confidence: 99%
“…The following definitions were used to estimate the number affected by level of severity, using the most affected eye: severe/advanced glaucoma—VA <3/60, vertical cup:disc ratio (VCDR) >0.8 and central visual field (CVF) of <10°; moderate glaucoma—any level of VA with VCDR >0.7 and CVF of 10–20°; early/mild glaucoma—any glaucomatous visual field defect and VCDR ≥0.7. Blind/end-stage glaucoma was defined as VA <3/60 in the better eye with a VCDR of 1.0 17. There are estimated to be 5900 (56%) adults per million population with severe/advanced disease, often blind in one eye and/or with severe visual impairment in the other eye, 2100 (20%) moderate cases, 400 (4%) early cases and a further 2100 (20%) are blind in both eyes.…”
Section: Glaucoma In Nigeriamentioning
confidence: 99%
“…These include low rates of early detection and diagnosis,17 lack of specialist equipment and treatment options, lack of specialist glaucoma clinics and care pathways, poor compliance with treatment and follow-up,9 the high cost of accessing care and treatment costs18 and lack of awareness and public knowledge about glaucoma compounded by socioeconomic deprivation 10. The number of eye health workers in Nigeria, including ophthalmologists and optometrists, falls short of WHO recommendations 19 20.…”
Section: Glaucoma In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation